Perubahan Kesadaran Berzakat, atas Pengaruh Video Iklan Layanan Masyarakat dan Dampaknya pada Masyarakat Jateng dan DIY - Bawono, Anton; Erlangga, Rifqi Aulia (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
This study aims to find out how much influence public service video ads have on zakat awareness. A total of 200 Muslim respondents from Central Java and Yogyakarta. The research method used is linear regression, which is processed with the help of SPSS 16.00 statistics. In addition to the study, a response was also made to the video on public service advertisements and a description of the awareness of the people of Central Java and Yogyakarta. From the findings, it was found that 19.2% of zakat awareness increased after watching a public service advertisement video. Positive findings are expected to be the light of the people of Central Java and Yogyakarta to immediately pay zakat. The amil zakat institution is also expected to be helped in terms of increasing the zakat conscious movement through mass media facilities